Intangible heritage as a social construction of authenticity: the example of Tunisian cuisine - Wadie Othmani (Via@)
This article offers a geographical study of the culinary heritage of Tunisia, a North African country in the Maghreb region, whose economy is strongly supported by the tourism sector. Thanks to the crossing, on the one hand, of the perimeter of production and development of a culinary culture inked through the succession of civilizations throughout the history of the country and, on the other hand, of the perimeter encompassing the Maghrebis (Tunisians, Algerians, Libyans and the diaspora) who currently consume spicy dishes (which characterize Tunisian cuisine) on a daily basis, the article proposes to determine the Territory of Tunisian Culinary Heritage (TTCH). He The article also suggests studying the link between generic places of consumption (hotels, restaurants, food trucks, snack bar, home, etc.) and the dishes consumed by tourists on vacation. The link thus obtained will be studied in relation to daily consumption practices through cultural, economic, family, etc. dimensions. This reasoning will show that the consumption strategy while on vacation is inevitably linked to daily consumption practices of all the tourists studied, either in a logic of rupture or of continuity. To reach the conclusions proposed in this article, the methodology followed is based on diversified survey tools (quantitative and qualitative) and combined statistical analyses (pivot table and chi-square tests).